A Rare Case of Bilateral Patellar Tendon Ruptures: A Case Report and Literature Review. (20th April 2016) - Tarazi, Nadim; O'loughlin, Padhraig; Amin, Amin; Keogh, Peter
Abstract : Bilateral patellar tendon ruptures are rare. The majority of case reports describing bilateral patellar tendon ruptures have occurred in patients with predisposing factors to tendinopathy. We describe a case of bilateral patellar tendon rupture sustained following minimal trauma by a patient with no systemic disease or history of steroid use. Due to the rarity of this injury, clinical suspicion is low. It is reported that 38% of patellar tendon ruptures are misdiagnosed initially. Therefore careful history taking and physical examination is integral in ensuring a diagnosis is achieved for early primary repair. We discuss the aetiology of spontaneous tendon rupture and report a literature review of bilateral patellar tendon ruptures.